Role definition is key—Rapid qualitative ethnography findings from a team‐based primary care transformation. Issue 3 (20th February 2019) - Brown‐Johnson, Cati; Shaw, Jonathan G.; Safaeinili, Nadia; Chan, Garrett K.; Mahoney, Megan; Asch, Steven; Winget, Marcy
Abstract: Purpose: Implementing team‐based care into existing primary care is challenging; understanding facilitators and barriers to implementation is critical. We assessed adoption and acceptability of new roles in the first 6 months of launching a team‐based care model focused on preventive care, population health, and psychosocial support. Methods: We conducted qualitative rapid ethnography at a community‐based test clinic, including 74 hours of observations and 28 semi‐structured interviews. We identified implementation themes related to team‐based care and specifically the integration of three roles purposively designed to enhance coordination for better patient outcomes, including preventive screening and mental health: (1) medical assistants as care coordinators; (2) extended care team specialists, including clinical pharmacist and behavioral health professional; and (3) advanced practice providers (APPs)—ie, nurse practitioners and physician assistants. Results: All stakeholders (ie, patients, providers, and staff) reported positive perceptions of care coordinators and extended care specialists; these roles were well defined and quickly implemented. Care coordinators effectively managed care between visits and established strong patient relationships. Specialist colocation facilitated patient access and well‐supported diabetes services and mental health care. We also observed unanticipated value: Care coordinators relayed encounter‐relevant chart information to providers while scribing; extended care specialists supported informal continuing medical education. In contrast, we observed uncertain definition and expectations of the APP role across stakeholders; accordingly, adoption and acceptability of the role varied. Conclusions: Practice redesign can redistribute responsibility and patient connection throughout a team but should emphasize well‐defined roles. Ethnography, conducted early in implementation with multistakeholder perspectives, can provide rapid and actionable insights about where roles may need refinement or redefinition to support ultimate physical and mental health outcomes for patients.